The Rapid Response of the Canada Basin to Climate Forcing: From Bellwether to Alarm Bells - Fiona McLaughlin; Eddy Carmack; Andrey Proshutinsky; Richard A. Krishfield; Christopher Guay; Michiyo Yamamoto-Kawai; Jennifer M. Jackson; Bill Williams (Oceanography, 2011)
Sea ice extent in the Arctic Ocean diminished significantly during the first decade of the 2000s, most particularly in the Canada Basin where the loss of both multiyear and first-year ice was greater than in the other three subbasins. Using data collected during basin-wide surveys conducted from 2003–2010 together with data collected during the 1990s and 2000s at one station in the southern Canada Basin, we investigate the response of the Canada Basin water column to this significant decrease in ice cover. Changes were evident from the surface down to the Atlantic layer: some changes were the result of Beaufort Gyre forcing on regional processes, others were the result of Arctic Ocean atmospheric forcing on a hemispheric scale and large-scale advection. These changes have troubling consequences for the ecosystem.